Serum levonorgestrel concentration and cervical mucus viscosity after six months of monoplant® implantation (Faculty of Medicine Universitas Indonesia, 2014)
Background: The use of levonorgestrel implants as a contraceptive method have undergone changes in the number of implants used, beginning from six rods in the early methods to two rods in the present method and have been proven effective. This study aims to evaluate the efficacy of single rod implant (Monoplant®) by measuring serum levonorgestrel concentration and cervical mucus quality. Methods: Thirty healthy women, aged 20-40 year old, and have been proven fertile, underwent single rod implant insertion. Levonorgestrel serum levels was measured every month and cervical mucus viscosity was examined every three month, until six months. Results: Levonorgestrel serum concentration was consistently above minimum effective level (200 pg/mL), from month 3 to 6 respectively 338.9 pg/mL, 424.8 pg/mL, 320.3 pg/mL, and 337.5 pg/mL. Almost all of the acceptors (96.7%) had good cervical mucus viscosity since three months following implant insertion. Conclusion: Levonorgestrel serum concentration in Monoplant® users was still above minimum contraceptive level until the sixth month. Viscosity of cervical mucus increased immediately following implant insertion. This indicates that single rod levonorgestrel implant is effective as a contraceptive method. Keywords: cervical mucus viscosity, implant monoplant®, serum levonorgestrel